Digital and Sharing Economy for Sustainable Development : A Bibliometric and Systematic Review - Osho, Awli; Evan, Lau (MDPI, 2023)
The concept of digitalization has become a common practice for adoption and integration across the economy in recent years. The rapid prospects of a spillover from digitalization quickly became the interest of countries and researchers, especially in the interest of sustainable development based on the SDGs of the United Nations. With several subsectors of the economy surfacing as a product of the digital economy, this study intends to identify the relationship between the digital economy and sharing economy, as well as their role in sustainable development. To achieve the objectives laid out, this study employs the use of bibliometric analysis and systematic literature review (SLR) to organize and extract the contents of the selected literature. The findings show that the contemporary sharing economy is driven by the digital economy and is reliant on its digital infrastructure, whereas there are mixed findings on the role of digitalization on sustainability.